2022
DOI: 10.2147/ijn.s364840
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism Intervention-Facilitated Nanomedicine Therapy

Abstract: Ordinarily, cancer cells possess features of abnormally increased nutrient intake and metabolic pathways. The disorder of glucose metabolism is the most important among them. Therefore, starvation therapy targeting glucose metabolism specifically, which results in metabolic disorders, restricted synthesis, and inhibition of tumor growth, has been developed for cancer therapy. However, issues such as inadequate targeting effectiveness and drug tolerance impede their clinical transformation. In recent years, nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 226 publications
0
12
0
2
Order By: Relevance
“…First, GOx consumes glucose and produces a large amount of H 2 O 2 , which provides the raw material for the Fenton reaction. 34 This reaction process was accompanied by a decrease in the environmental pH value due to gluconic acid production. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, GOx consumes glucose and produces a large amount of H 2 O 2 , which provides the raw material for the Fenton reaction. 34 This reaction process was accompanied by a decrease in the environmental pH value due to gluconic acid production. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, a series of changes cause tumour cells to reregulate adenine nucleoside triphosphate (ATP) production or increase glucose uptake to promote energy production. Under sufficient oxygen, tumour cells promote the rapid energy supply of glycolysis due to the change in the microenvironment, which is called the “Warburg effect” [ 172 , 173 ]. Metabolic reprogramming in the TME was confirmed by analysing the metabolic-related gene prognostic index (MRGPI) in HNSCC.…”
Section: Modulation Of Cell Death In Hnsccmentioning
confidence: 99%
“…The first method mentioned in the glycolysis inhibition strategy can also be recognized as glucose starvation, which has emerged as a promising method to inhibit the metabolism and growth of cancer cells. [ 27–36 ] For example, Seki et al. reported that upon cold exposure, the resulting activated brown adipose tissue can consume glucose, and thus the tumor glucose supply is limited, as a result of which the tumor growth of the mice exposed to cold condition is significantly inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…[15,26] The first method mentioned in the glycolysis inhibition strategy can also be recognized as glucose starvation, which has emerged as a promising method to inhibit the metabolism and growth of cancer cells. [27][28][29][30][31][32][33][34][35][36] For example, Seki et al reported that upon cold exposure, the resulting activated brown adipose tissue can consume glucose, and thus the tumor glucose supply is limited, as a result of which the tumor growth of the mice exposed to cold condition is significantly inhibited. [16] Besides, a commonly used glucose scavenger is the glucose oxidase (GOx), which can catalyze glucose into gluconic acid and hydrogen peroxide (H 2 O 2 ) in the presence of oxygen (O 2 ) and has gained wide attention for its remarkable anticancer capability via not only metabolism inhibition (by glucose consumption) but also cell killing (by H 2 O 2 generation).…”
Section: Introductionmentioning
confidence: 99%